2019
DOI: 10.1038/s41598-019-44687-1
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of methane in supercritical carbon dioxide across the Widom line

Abstract: Diffusion of methane diluted in supercritical carbon dioxide is studied by experiment and molecular simulation in the temperature range from 292.55 to 332.85 K along the isobars 9.0, 12.5 and 14.7 MPa. Measurements of the Fick diffusion coefficient are carried out with the Taylor dispersion technique. Molecular dynamics simulation and the Green-Kubo formalism are employed to obtain Fick, Maxwell-Stefan and intradiffusion coefficients as well as shear viscosity. The obtained diffusion coefficients are on the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…One of the first observations of a change in slope or even the appearance of a V-shaped region on a diffusion curve was reported by Nishiumi& Kubota [ 18 ], who attributed this to a decrease in thermodynamic factor. Recent molecular dynamic simulations also showed that the thermodynamic factor in mixtures manifests a deep well in the vicinity of the Widom line [ 8 ]. At the critical point, the thermodynamic factor is zero per definition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the first observations of a change in slope or even the appearance of a V-shaped region on a diffusion curve was reported by Nishiumi& Kubota [ 18 ], who attributed this to a decrease in thermodynamic factor. Recent molecular dynamic simulations also showed that the thermodynamic factor in mixtures manifests a deep well in the vicinity of the Widom line [ 8 ]. At the critical point, the thermodynamic factor is zero per definition.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that the Fick diffusion coefficient in scCO 2 may vary strongly at low solute concentrations, for example, in the case of methane [ 8 ]. It can be also noted that the content of quinine used in medical and industrial products is very low, for example, tonic water contains slightly less than 0.01% quinine by mass fraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common methods at an early stage of studying supercritical fluids’ properties is molecular dynamics (MD), which is a bridge between experimentally observed macroscopic properties of a substance with microscopic ones. This approach has been previously used to study the Widom delta separating the region of liquid-like from gas-like SCF in the p-T diagram [ 53 , 54 , 55 ]. Molecular dynamics (MD) is a method used for numerical simulation of the system evolution in time by integrating the equations of motion of atoms or particles.…”
Section: Methodsmentioning
confidence: 99%
“…The results of a molecular simulation study of methane and small aromatics infinitely diluted in supercritical CO 2 at different temperatures, pressures, and compositions are discussed. In the Widom region, an anomalous behavior of the Fick diffusion coefficient and other transport properties was found even for methane diluted in CO 2 [1].…”
Section: P669 Fluidverfahrenstechnikmentioning
confidence: 98%